Facile supramolecular strategy to construct solid fluorophore@metal–organic framework composites. Issue 16 (27th July 2022) - Trifoi, Lavinia A.; Hodgson, Gregory K.; Dogantzis, Nicholas P.; Soha, Sumaiya A.; Dayam, Roya M.; Antonescu, Costin N.; Botelho, Roberto J.; Wylie, R. Stephen; Impellizzeri, Stefania
Abstract : The synthesis of a zeolitic imidazolate framework in the presence of a fluorophore enables the capture of the guest dye within the MOF and yields a material with high solid-state emission, enhanced fluorescence lifetime and increased photostability. Abstract : The design and synthesis of a microporous construct based on the entrapment of an emissive fluorescein derivative in a zinc 2-methylimidazolate (ZIF-8) metal–organic framework (MOF) is detailed. Synthesis of the MOF in the presence of a fluorophore enables the capture and dispersal of dye molecules within the framework. Within the resulting supramolecular assemblies, the fluorophore components show excellent photophysical properties such as high emission and increased fluorescence lifetime, despite the tendency of the dye to undergo aggregation-caused quenching in the solid-state, as well as a 4-fold enhancement of the fluorophore's photostability. The demonstration that supramolecular events can be invoked to construct solid fluorescent systems from separate components is realized. The encapsulation of the fluorescein in an enclosed subunit of the ZIF-8 framework was modelled using the density-functional tight-binding method. Furthermore, the fluorophore@MOF composite can be internalized by mammalian macrophage cells and transported to lysosomes without disrupting cell viability. In principle, this simple protocol can evolve into a general strategy for intracellular delivery of functional molecular components for targeted bioimaging or theranostic applications.